2015
DOI: 10.1038/srep09819
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Protection of N-Acetylcysteine and Ascorbic Acid 2-Phosphate on Human Mesenchymal Stem cells Against Mitoptosis, Necroptosis and Apoptosis

Abstract: Human mesenchymal stem cells (hMSCs) contribute to ischemic tissue repair, regeneration, and possess ability to self-renew. However, poor viability of transplanted hMSCs within ischemic tissues has limited its therapeutic efficiency. Therefore, it is urgent to explore new method to improve the viability of the grafted cells. By using a systematic analysis, we reveal the mechanism of synergistic protection of N-acetylcysteine (NAC) and ascorbic acid 2-phosphate (AAP) on hMSCs that were under H2O2-induced oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 51 publications
2
55
1
Order By: Relevance
“…In our study, we found that inhibiting necroptosis evidently reduced intracellular ROS levels and raised ΔΨm levels, which indicated that the PARP‐AIF pathway might be a downstream component of RIP1/RIP3‐mediated programmed necrosis in H 2 O 2 ‐induced NP cells death. In addition, oxidative stress has been shown to induce cell death in human bone mesenchymal stem cells (BMSC) and hepatocellular carcinoma cells through PARP hyperactivation‐mediated necroptosis . However, there have been no reports indicating whether the PARP‐AIF pathway is involved in H 2 O 2 ‐mediated NP cells death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, we found that inhibiting necroptosis evidently reduced intracellular ROS levels and raised ΔΨm levels, which indicated that the PARP‐AIF pathway might be a downstream component of RIP1/RIP3‐mediated programmed necrosis in H 2 O 2 ‐induced NP cells death. In addition, oxidative stress has been shown to induce cell death in human bone mesenchymal stem cells (BMSC) and hepatocellular carcinoma cells through PARP hyperactivation‐mediated necroptosis . However, there have been no reports indicating whether the PARP‐AIF pathway is involved in H 2 O 2 ‐mediated NP cells death.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, oxidative stress has been shown to induce cell death in human bone mesenchymal stem cells (BMSC) and hepatocellular carcinoma cells through PARP hyperactivation-mediated necroptosis. 18,50 However, there have been no reports indicating whether the PARP-AIF pathway is involved in H 2 O 2 -mediated NP cells death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, MCA also helped hMSCs to cope with H 2 O 2 -induced cell death by inhibiting cell death and maintaining mitochondria integrity [16]. …”
Section: Discussionmentioning
confidence: 99%